An international comparative perspective on affective organizational commitment predictors’ - Tavares, S. M.; Caetano, António (Identity and Diversity in Organizations, 2003)
The present study aims to identify some of the variables that influence the development of affective organizational commitment in an inter-organizational and cross-cultural context, filling some of the gaps observed in the literature. In order to analyze this, it was developed a cross-national research, with representative samples of the population of four countries: Portugal (600), Japan (407), .EUA (526), and Sweden (448). Multiple regression analyses were conducted in order to estimate the influence of each independent variable on affective OC. The obtained models of analysis allowed the explanation of a substantial part of the variance of OC in each country (between 30% and 39%). The results revealed that globally the pattern of variables predicting OC is identical in the four countries. Thus, the variables with more power to predict OC have proved to be job enrichment and the good quality of relational climate at work. However, regarding the variables with less influence on OC, some differences were observed which might express some particularities concerning the respective national contexts